Dual Organophosphate and Paraquat Poisoning: Successful Management with Early Hemoperfusion and Ventilation: A Case Report - Yelanati, Ramesh; Moturu, Dharanindra; Potineni, Ramesh Babu; Rayana, Supriya; Shaik, Mohammad Noor; Thommandru, Sravani; Devaki, Kondaveeti; Sruthi Grandhi, Kavya; Naga Pavani Pucha, Jahnavi (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Organophosphate poisoning is a major public health issue in many low and middle-income countries. Paraquat, a widely used herbicide, can often cause severe, usually fatal poisoning in humans. Dual poisoning involving both organophosphates and paraquat is rare. Case Presentation: A 17-year-old male who ingested both substances was admitted to the emergency department intensive care unit. He was treated with four sessions of hemoperfusion, along with intravenous atropine and pralidoxime. After the fourth hemoperfusion, the patient developed respiratory distress due to acute cholinergic syndrome secondary to organophosphate poisoning, requiring endotracheal intubation. By day five, his clinical condition improved, and he was extubated. Six hours after extubation, he developed sudden respiratory distress and was re-intubated with a 7.5 mm endotracheal tube and connected to a mechanical ventilator. The patient was diagnosed with intermediate syndrome secondary to organophosphate poisoning, and atropine infusion was restarted. By day seven, his condition improved and he was successfully weaned off ventilation. He was discharged hemodynamically stable on day 10. Conclusion: This mixed organophosphate-paraquat poisoning case was clinically complex and challenging. Management involved a combination of mechanical ventilation and hemoperfusion, which had to be carefully titrated. Further studies are needed to improve treatment protocols and outcomes for mixed poisoning cases.